Adherence to disease modifying therapies in patients with multiple sclerosis - Pileckė , D.; Giedraitienė , N. (Neurologijos seminarai, 2019)
Introduction. Multiple sclerosis is an inflammatory demyelinating disease of the central nervous system. Disease modifying treatment tends to reduce the risk for relapses rate and disease progression, therefore adherence to treatment is essential for outcome.Aim of the study. To examine adherence to disease-modifying therapy in multiple sclerosis patients and identify the factors affecting it.Material and methods. The research was conducted in 2019 at Vilnius University Hospital Santaros Clinics Neurology department using an anonymous questionnaire. Statistical data analysis was performed on IBM SPSS. P value
Keywords: multiple sclerosis; disease-modifying therapy; adherence